2018
DOI: 10.1177/0022042618795138
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Motives, Perceived Norms, and Adolescents’ Drinking

Abstract: Various cognitive and social factors influence the consumption of alcohol during adolescence. Accurate assessment of the relative importance of these variables is crucial for planning interventions against alcoholrelated problems. This study compared the effects of drinking motives, perceived parent, and peer alcohol consumption on alcohol use in Italian adolescents. We collected the data by means of a self-report questionnaire on a sample of 229 secondary school students who were 15-20 years old. To test the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Hence, individuals drink to obtain positive outcomes or to avoid negative consequences, and they are motivated by internal or external rewards. Accordingly, four categories of drinking motives emerge as final antecedents of drinking behavior: 1. enhancement: to heighten mood or wellbeing (internally generated with positive valence); 2. social: to obtain social rewards (externally generated with positive valence); 3. coping: to attenuate negative emotions (internally generated with negative valence); 4. conformity: to avoid social rejection (externally generated with negative valence) (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, individuals drink to obtain positive outcomes or to avoid negative consequences, and they are motivated by internal or external rewards. Accordingly, four categories of drinking motives emerge as final antecedents of drinking behavior: 1. enhancement: to heighten mood or wellbeing (internally generated with positive valence); 2. social: to obtain social rewards (externally generated with positive valence); 3. coping: to attenuate negative emotions (internally generated with negative valence); 4. conformity: to avoid social rejection (externally generated with negative valence) (8).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, drinking motives can shape drinking patterns, with enhancement and coping motives being the most correlated with ABD (4,(8)(9)(10). The re-enactment of the determinant framework appears to be crucial to the evaluation of the concerning consequences in adolescence, given the "still-going-on" maturation of the brain and the major vulnerability to alcohol during neurodevelopment (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Data were collected using a validated researcher-administered questionnaire, adapted from studies conducted among high school learners [ 17 , 19 , 56 ] and on motivations for alcohol use [ 34 , 36 ]. Data collected included the demographics, accessibility, motivations and effects of alcohol use among learners.…”
Section: Methodsmentioning
confidence: 99%
“…Adolescence is a developmental period of heightened responsiveness to social rewards, and this implies an increasing desire to fit in among peers [ 33 ]. Drinking motives and perceived peer and parental norms are strong predictors of alcohol use [ 34 ]. Identifying the adolescents’ motivations for their alcohol use has revealed that adolescents consume alcohol when they are having fun with their friends.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation